IMPLEMENTASI HACCP PADA PEMBEKUAN FILLET IKAN ANGGOLI (Pristimopoides multidens) BENTUK SKIN ON (Studi Kasus Pada PT. Sulindo Kota Probolinggo) - Ramli Ramli; Abdul Muqsith (Universitas Bengkulu, 2022)
The fishery product processing industry must comply with and implement the Quality Assurance and Safety System for Fishery Products so that the products produced provide quality assurance and food safety for consumers and as an effort to meet the demands of the export market. The conception of the Quality Assurance and Safety of Fishery Products method that can be applied to the processing of fishery products is the Hazard Analysis Critical Control Point (HACCP). This study aims to determine the implementation of HACCP on freezing of fillets angoli fish (Pristimopoides multidens) in the form of skin on at PT. SULINDO. The method of data collection was carried out by the survey method. The data obtained and analyzed consisted of primary and secondary data. Data were obtained by conducting interviews and direct observations in the field, in the form of hazard analysis, identification of critical control points and supervision of critical control points and physical testing. The results of the research show that the implementation of HACCP on freezing of fillets angoli fish (Pristimopoides multidens) in the form of skin on at PT. SULINDO consists of 12 steps, which include compiling a HACCP team, describing products, identifying product uses, verifying flow charts, conducting hazard analysis and preventive actions, determining Critical Control Points (CCP), determining critical limits, establishing monitoring systems, establishing corrective actions, establish verification procedures, establishing storage and documentation procedures. Based on decision tree, Critical Control Point (CCP) at the freezing stage of fillet Anggoli fish (Pristimopoides multidens) is in the form of skin on at PT. SULINDO, there is only one process stage that is designated as a Critical Control Point (CCP), namely the stage of detecting metals with a significant form of metal fragments in fillet with a critical metal limit applied for prevention, namely Fe 2.5 mm and Non Fe 2 ,5 mm and monitoring measures were carried out on the possibility of Fe metal flakes using a metal detector or sensitivity using a metal taster every hour. Keywords : HACCP implementation, freezing of fillet angoli fish